Electro‐Optical Detection of Single Molecules Based on Solid‐State Nanopores. Issue 1 (16th August 2020) - Lu, Wenlong; Hu, Rui; Tong, Xin; Yu, Dapeng; Zhao, Qing
Abstract : Electrical detection of single molecule based on solid‐state nanopores is recently combined with optical methods. The synergistic effect of the electrical and optical measurements makes the combination powerful. It is promising for the next‐generation single‐molecule detection approach. Conventional solid‐state nanopore sensors monitor the electrical pulses caused by molecules translocating through the nanopore. However, the electrical signal is limited by insufficient resolutions, low throughput, lack of specificity, and molecule manipulation. Optical detection of single molecules has been extensively studied since the past decades. Optical signals, such as surface‐enhanced Raman spectroscopy (SERS) and fluorescence, have unique sensitivity and specificity of single molecules. Recently, optical methods are developed to complement the limitations of electrical detection of solid‐state nanopores. This review describes the main approaches used for electro‐optical detection of single molecules based on solid‐state nanopores, including total internal reflection fluorescence (TIRF), confocal microscopy, and plasmonic nanostructures. Laser‐induced heating, optical trapping, and strategies to reduce background fluorescence are also discussed. Moreover, recent experiments on electro‐optical detection of DNA and other analytes are introduced. Abstract : Solid‐state nanopores are recently combined with optical sensors for synchronous electro‐optical detection of single molecules. This review discusses different optical configurations and nanostructures that are integrated with solid‐state nanopores, including total internal reflection fluorescence (TIRF), confocal microscopy, zero‐mode waveguides (ZMWs), and other plasmonic nanostructures. Recent development on electro‐optical detection of DNA and other analytes are introduced as well.